The humanization of global politics : international criminal law, the responsibility to protect, and drones - Gholiagha, Sassan, 1984- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
This book observes a growing humanisation of global politics relating to the appearance of individual human beings in discourses of global politics. It identifies a mismatch concerning International Relations theory and International Law and the study of the humanisation of global politics. To overcome this mismatch, Sassan Gholiagha proposes a novel theoretical framework based on feminist and constructivist International Relations theory and non-statist theories of International Law scholarship. The book applies this interdisciplinary framework together with an interpretative analytical framework to three cases: the discourse on prosecution, studying international criminal law and the work of the International Criminal Court; the discourse on protection, focusing on the Responsibility to Protect; and the use of drones in targeted killing operations. Drawing on these case studies and the frameworks, the book identifies how individual human beings as participants in global politics position themselves and are positioned by others in these various discourses.
The humanisation of global politics -- Humanisation in IR theory and international law -- The social construction of the individual human being - A conceptual and a theoretical framework -- Guilty and innocent : the individual human being in International Criminal Law -- Heuristics and positions : a framework for analysing discourses of humanisation -- Protecting the individual human being from mass atrocities -- Killing the individual human being via drones -- The individual human being as a theoretical category - A conclusion and an outlook.
Title from publisher's bibliographic system (viewed on 02 Sep 2022).
Keywords: International law and human rights; International criminal law